Eliminating cross interference between multiple receivers to achieve targeted power distribution for a multi‐frequency multi‐load MCR WPT system. Issue 8 (6th June 2018) - Liu, Fuxin; Yang, Yong; Ding, Ze; Chen, Xuling; Kennel, Ralph M.
Abstract : Simultaneous non‐contact energy transmission for multiple loads with separate receiving coils is a remarkable advantage of magnetically coupled resonant (MCR) wireless power transfer (WPT). A novel multi‐frequency driver configuration for MCR WPT system with multiple loads is proposed, where the receiving resonant tanks are severally tuned at different resonant frequencies to make the loads selective. A methodology of adjusting the resonant frequency of the transmitter is presented to satisfy diverse energy requirements of specific loads. However, the cross interference from non‐targeted frequencies inherently exerts an influence between multiple receivers, and thus makes power allocation non‐constrained through multi‐coupling channels, which increase the difficulty of power control and parameters design. In order to reduce and further eliminate the influences of the cross interference and realise targeted power distribution for selective loads, three types of parallel and series resonant compensation circuits are introduced into receivers. By flexibly utilising the impedance characteristics of parallel and series resonant networks, the proposed compensation circuits are proved to be effective, significantly reducing the cross interference and exclusively delivering power to the selective loads corresponding to pre‐tuned resonant frequencies. Finally, the experimental results from a prototype have confirmed the effectiveness of the proposed methods.